Comparative flank wear and produced chips types analysis of CNMG 120408 indexable cutting inserts after machining hardened 1.6582 steel - Šramhauser, Karel; Kraus, Pavel; Černý, Pavel; Kříž, Pavel; Špalek, František; Horký, Roman; Zoubek, Tomáš; Vochozka, Vladimír (Frontiers in Materials, 2024)
IntroductionThe marking of interchangeable cutting inserts according to ISO 6987 does not include the know-how of cutting tool manufacturers in the design of chip-breakers or the application of coatings. These small differences have a key effect on the efficiency and service life of cutting tools and result in qualitative and quantitative differences in production, which is related to the reduction or increase in costs associated with the appropriate choice of cutting tool. The design of the inserts also affects the shape and size of the chips produced, which is important to monitor for a safe machining process and subsequent waste management. This research deals with the effect of selected factors on the tool life and the form of the chips produced.MethodsIndexable cutting inserts of the type CNMG 120408 from three different manufacturers were tested for their lifetime under identical cutting conditions (vc = 80 m s−1, ap = 1.5 mm, f = 0.3 mm·ot−1) on steel 1.6582 hardened to 40–44 HRC. These inserts are made of sintered tungsten carbide in a cobalt binder, coated with Al2O3 and TiCN layers. During machining, the wear of the main flank was continuously measured until the critical wear rate VBmax = 0.3 mm was reached. At the same time, the produced chips were continuously collected and analyzed in terms of their shape and size. The number of chips produced per 100 g of chips was calculated to obtain an analogous value indicating the total chip collection in terms of waste management. The SEM was used to identify both the types of coating layers present on the investigated inserts and the types of wear observed after reaching critical wear.ResultsThe longest lifetime was achieved by the PM 4325 insert coated by 11.5 ± 1.2 µm TiCN layer and 5.3 ± 0.3 µm Al2O3 layer with a time T = 19.5 min. The chips produced were in the forms of arch connected and arch loose and the average chip length was 27.9 ± 7.6 mm. The number of chips per 100 g produced by the PM 4325 was 1,494 ± 401 pieces, which was the lowest count of chips within the experiment (which is not optimal). The MP3 -WPP20S insert coated by 17.8 ± 0.4 µm TiCN layer and 15.1 ± 0.3 µm Al2O3 layer achieved lifetime T = 17.4 min even though it has twice the thickness of the coating compared to PM 4325. Produced chips in the forms of arch connected, arch loose and tubular short shape and the average chip length was 34.1 ± 5.5 mm, which was the worst chip length result within the experiment in terms of chip evaluation. The number of chips per 100 g produced by MP3 -WPP20S was 1,520 ± 401 pieces. The E-M GRADE T9325 insert coated by 7.2 ± 0.5 µm TiCN layer and 5.1 ± 0.2 µm Al2O3 layer achieved the shortest lifetime with a time T = 10.8 min. The chips produced were arch loose in shape, with an average chip length of 8.2 ± 0.7 mm. The number of chips per 100 g produced by the E-M GRADE T9325 was 2,392 ± 259 pieces, achieving the best result in the experiment in terms of chips produced. The achieved results are correlated with different combinations of thicknesses of Al2O3 and TiCN protective coatings revealed by SEM analysis.Discussion/ConclusionTogether with the geometrical nuances of the design of the different manufacturers, factor of combinations of coatings thicknesses has an influence on the variation of the wear progress and the achievement of a specific lifetime value of the cutting inserts. The experiment concludes that the thickness of the coating layers alone does not have a direct effect on the overall lifetime of the tool, and the approximate lifetime of the cutting edge cannot be predicted based on the parameters of the coating layers. When choosing a cutting tool, the manufacturer should carry out a test series for the specific material to be machined, despite the declaration of the composition and thickness of the coating layers. The analysis of the produced chips led to the conclusion that the wafers with a thinner coating layer, especially the Al2O3 layer, formed better chips in terms of their shape and size due to the different heat distribution during machining.